Intelligence Towel Dryer & Disinfectant / Muhamad Azzim Hakimi Abdul Ghani ... [et al.] - Abdul Ghani, Muhamad Azzim Hakimi; Alim, Hendrry Win; Mokhter, Suriyati; Zairol Anuar, Nadia Emylia; Mohd Hilmi, Farhana Nabilah (2018)
Germs or bacteria are more likely to growth on a wet surface and we will be at a risk of getting a disease if we are exposed to bacteria. Without our concern, we use a thing that brings a lot of germs every day which towel is. So, how long does it take for the towel to completely dry and how confident we are that our towel brings least of germs? So here is the Intelligence Towel Dryer & Disinfectant with UV light technology will help to dry the towel much sooner and disinfecting the towel. So, their towel cannot be dried as fast as those who opt for outdoor drying. Besides, most students who stay in hostel also have a problem with wet and smelly towel due to no space to hang their towel. Most of them just hang their towel in a bathroom and let it dry on their own. The most effective way to dry and disinfect the wet towel naturally is by hanging the towel under the sun light as it will emits an ultraviolet that can help in kill the germs. This theory will be implemented into this new technology to dry and disinfect the towel even in a closed and dark room.